Common fixed point of mappings satisfying rational inequality in Complex valued b-metric spaces - Dubey, A. K.; Mishra, Urmila (Communications in Mathematics and Applications, 2017)
In this paper, we prove some common fixed point theorems satisfying rational inequality in complex valued b-metric spaces. The presented theorems extend, generalize and improve the corresponding result of Rouzkard and Imdad. Also, an example is given to illustrate our obtained result.